Pola Relasi Sosial Keagamaan Mahasiswa Aktivis di Kota Samarinda: Studi Kasus Badan Eksekutif Mahasiswa Isntitut Agama Islam Negeri Samarinda dan Badan Eksekutif Mahasiswa Universitas Mulawarman Samarinda - Widiarto, Sri (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Social Relation Pattern of College Activists, between ideal and reality is the existence of very interesting problem to investigate which has something to do with ghairu mahdah (common ritual) because of the following factors: there are some students who less understand Islamic principles in comprehensive way, some students are less creative in packaging of Islamic activities; some students are less interested in Islamic Studies at campus and some others have less commitment in the implementation of Islamic values. Problem of this research is how is the religious social relation pattern of college activists in Samarinda? and what are the factors to affect religious social relation pattern of college activists in Samarinda? This case study research uses qualitative descriptive approach. Data collection technique was done by using observation, interview, and documentation. Data of this research is analyzed by using triangulation. It was done by reduction through induction and deduction process of observation transcripts, interview, and documentation of individual case, and it is compared in cross case analysis in discussion, and it was concluded as a research finding. This research reveals two conclusions. Firstly, religious social relation pattern of college activists in Samarinda of Students’ Executive Council of State Islamic Institute of Samarinda and Students’ Executive Council KM of Mulawarman University Samarinda individually are internal board management; external board management; peoples who gives contributions to the college; people who play role in the family; influencial people in society. In terms of organization, to develop religion, establish cooperation with attitude and develop relevant programs. Secondly, factors which affect religious social relation pattern of college activists in Samarinda of Students’ Executive Council of State Islamic Institute of Samarinda and Students’ Executive Council KM of Mulawarman University Samarinda are Islamic and general education factor; family and environment factor, awareness factor, and social media factor.",